(untitled) (Universal International Scientific Journal, 2026)
This article describes how corporate social responsibility affects the psychological state, motivation and work performance of employees. The role of corporate social responsibility in improving job satisfaction, commitment and employee morale among employees is very significant. Compliance with social and environmental responsibilities of companies enhances positive psychological effects among employees, including increased motivation and job satisfaction. The article also analyzes the impact of corporate social responsibility strategies on communication with employees and their mental health.